Sodium amide as a "zero dead mass" sacrificial material for the pre-sodiation of the negative electrode in sodium-ion capacitors. (10th April 2021) - Jeżowski, P.; Chojnacka, A.; Pan, X.; Béguin, F.
Highlights: Sodium is fully and irreversibly extracted from NaNH2 by electrochemical oxidation. The NaNH2 oxidation liberates gases, without any remaining dead-mass in the electrode. Sodium extracted from a NaNH2 -activated carbon electrode is inserted in hard carbon. An AC//HC-Na hybrid capacitor is obtained after the sodium transfer to hard carbon. The AC//HC-Na capacitor displays 4 times higher specific energy than an AC/AC EDLC. Abstract: The galvanostatic oxidation/reduction of a sodium amide (NaNH2 )-activated carbon (AC) composite electrode has been studied vs. sodium counter/reference electrode with 1 mol L −1 NaClO4 ; EC:PC (ethylene carbonate:propylene carbonate, 1:1 in volume) electrolyte. The irreversible oxidation capacity of NaNH2 reached a value of 680 mAh g −1 at ~ 3.8 V vs. Na + /Na, which is close to the theoretical capacity of 686 mAh g −1 . The internal pressure increase during the positive polarization of the NaNH2 -AC electrode, as well as the ex-situ electrode gravimetric measurements after the polarization, confirmed the evolution of gaseous by-products (N2 and H2 ). Owing to its high irreversible capacity, NaNH2 could be used as low amount (only 25 wt%) sacrificial material added to AC (55 wt%) in a NaNH2 -AC//HC (hard carbon) cell with 1 mol L −1 NaClO4 ; EC:PC electrolyte. During the positive polarization of the NaNH2 -AC electrode, sodium was irreversibly extracted and inserted into HC, giving rise to an AC//HC-Na sodium-ion capacitor (NIC). In the voltage range from 2.2 V to 3.8 V, the obtained NIC demonstrated a discharge capacitance of 35 F g −1 (with a capacitance retention of 92% after 5000 cycles) and a value of specific energy of 35 Wh kg −1 at 1 kW kg −1 (per total active mass of the two electrodes), which is almost four times higher than the specific energy (9 Wh kg −1 at 1 kW kg −1 ) of an electrical double-layer capacitor (EDLC) with the same AC used for electrodes and operating in the same electrolyte up to 2.7 V.